Study on the Occurrence of Double Bottom Simulating Reflectors in the Makran Accretionary Zone - Jiangxin Chen; Wenyu Zhao; Siyou Tong; Leonardo Azevedo; Nengyou Wu; Bin Liu; Huaning Xu; Jianming Gong; Jing Liao; Jie Liang; Dongxu Luo; Yu Fu (Journal of Marine Science and Engineering)
A Bottom Simulating Reflector (BSR) is a seismic feature closely related to marine gas hydrate as it is usually regarded as the seismic response of the base of the gas hydrate stability zone in seismic profiles. BSRs are widely distributed in the Makran accretionary wedge, and double BSRs are observed at some locations. Double BSRs usually appear on seismic profiles as two layers of BSRs located at distinct depths but with large lateral seismic amplitude variations. Based on the multi-channel seismic reflection data acquired over the Makran accretionary wedge, this work studies the origin of the double BSR in the Makran accretionary wedge and its association with fluid escape events. Our modeling suggests that double BSRs correspond to both the paleo-seafloor and modern seafloor caused by late sedimentary activities. Also, the residual paleo-BSR migrates upward due to the increase in local geothermal gradient caused by diapirs and gas chimney thermal fluids.